Social literacy practices of Afghan and Somali refugees in a transitional setting - Othman, Juliana; Wei, Lim Jia (Universitas Syiah Kuala, 2024)
The purpose of this paper is to explore the social literacy practices of Afghan and Somali refugees in a transitional context. Although refugees have been the subject of previous research in various domains, our understanding of their literacy practices in urban areas, particularly in Malaysia, is still limited. The lack of literacy research in this setting exposes a gap in the current literature aimed at better understanding refugee literacy practices in a transitional situation. Thus, this study examines urban refugee literacy experiences via the lens of literacy as a social practice. It was exploratory in nature and used a qualitative methodology. Face-to-face interviews with four refugees were conducted at two community centres to collect primary data. In addition, field notes based on community centre visits provided by the participants were used as a secondary data source in the study to understand the literacy experiences of the participants better. The findings indicated that participants enacted literacy practices in their transitional setting for three primary purposes: to increase their funds of knowledge, to enact personal agency, and for community building. These results challenge the stereotype that refugees are powerless and highlight avenues or ways in which refugee communities can be supported in a transitional context.